A survey on doctors' cognition of depression in patients with epilepsy. Issue 8 (4th June 2021) - Peng, Weifeng; Ding, Jing; Zhan, Shaokang; Wang, Xin; ,
Abstract: Objective: This survey aimed to assess doctors' cognition on depressive symptoms in patients with epilepsy in Shanghai China. Methods: Questionnaires were handed out to doctors who have taken part in the epilepsy care, covering those from all third‐grade hospitals and several second‐grade hospitals in Shanghai China. Respondents were asked to make choices for their demographic profiles, clinical practices, acquired knowledge of, and attitudes toward the comorbidity of epilepsy and depression. Results: A total of 282 questionnaires were collected from 16 hospitals in Shanghai China, of which 280 copies were included in the statistical analysis. Respondents were mainly less than 50 years (260, 92.8%), mostly residents and attendings (206, 73.6%), and mostly master and doctor's degrees (225, 80.3%). The ratio of epileptologists and nonepileptologists was 56 (20.1%):224 (79.9%). Compared to nonepileptologists and residents, epileptologists and doctors with higher professional titles were more likely to answer that they received a higher percentage of patients with the comorbidity of epilepsy and depression (≥30%), and they knew very well about the knowledge, and held the view that depression exacerbated seizures ( p  < .05). Surprisingly, most doctors including chief doctors and epileptologists answered that they had difficulties in prescribing antidepressants. Quite a few doctors from lower class hospitals even preferred to use tricyclic antidepressants for controlling depressive symptoms in patients with epilepsy. Significance: Doctors, especially younger doctors and nonepileptologists, need more training to get knowledge of the comorbidity of epilepsy and depression. However, the therapeutic methods for depressive symptoms in patients with epilepsy were still limited and in a challenge. Abstract : A questionnaire‐based doctor survey was developed to investigate the knowledge of and attitudes towards the comorbidity of epilepsy and depression in Shanghai China. Epileptologists and doctors with higher professional titles have better knowledge and hold the view that depression exacerbates seizures. Most doctors including chief doctors and epileptologists answer that they have difficulties in prescribing antidepressants, indicating the therapeutic methods for depressive symptoms in patients with epilepsy are still limited and in challenge.